Pengaruh Suasana Kelas yang Kondusif dan Berbasis Iman terhadap Peningkatan Motivasi Belajar Siswa Dalam Mata Pelajaran Pendidikan Agama Kristen di SD Kania Tangerang Banten - Wallangara, Yoser Yoli; Paparang, Stenly Reinal (JURNAL KADESI, 2025)
This study aims to determine the effect of a conducive and faith-based classroom atmosphere on students' learning motivation in Christian Religious Education at SD Kania Tangerang, Banten. The background of this study stems from the importance of Christian religious education in shaping students‘ character and spirituality, as well as the need for high learning motivation to support the success of the learning process. A positive and faith-based classroom atmosphere is believed to enhance students’ comfort, participation, and enthusiasm in learning. The research method used in this study is quantitative with a descriptive approach and statistical analysis of correlation and regression. Data were collected through the distribution of questionnaires to 68 students and analysed using SPSS 26 software and Microsoft Excel. The results of the study indicate that there is a significant relationship between classroom atmosphere and students‘ learning motivation, with a correlation coefficient of r = 0.381 and p = 0.001. Additionally, classroom atmosphere contributes 14.5% to the variation in students’ learning motivation. These findings indicate that a conducive and faith-based classroom atmosphere, characterised by positive interactions between teachers and students and the application of Christian values in learning, contributes significantly to improving student learning motivation. This study recommends that educators continue to create a learning environment that is supportive physically, psychologically, and spiritually, in order to encourage students to grow in faith and enthusiasm for learning.